Enhanced third harmonic generation in ultrathin free-standing β-Ga2O3 nanomembranes: study on surface and bulk contribution. Issue 1 (14th December 2021) - Yi, Gao; Jeon, Sangheon; Kwon, Young Woo; Park, Jongkyoon; Nguyen, Duy Anh; Suchand Sandeep, C. S.; Hwang, Wan Sik; Hong, Suck Won; Kim, Seungchul; Kim, Young-Jin
Abstract : Third harmonic generation from freestanding and glass-supported ultrathin β-Ga2 O3 nanomembranes. The surface and bulk contributions of nonlinear optical harmonic generation. Abstract : Third harmonic generation (THG) has proven its value in surface and interface characterization, high-contrast bio-imaging, and sub-wavelength light manipulation. Although THG is observed widely in general solid and liquid substances, when laser pulses are focused at nanometer-level ultra-thin films, the bulk THG has been reported to play the dominant role. However, there are still third harmonics (TH) generated at the surface of the thin-films, not inside the bulk solid – so-called surface TH, whose relative contribution has not been quantitatively revealed to date. In this study, we quantitatively characterized the surface and bulk contributions of THG at ultra-thin β-Ga2 O3 nanomembranes with control of both the laser and thin-nanomembranes parameters, including the laser peak power, polarization state, number of layers, and nanomembranes thicknesses. Their contributions were studied in detail by analyzing the TH from freestanding β-Ga2 O3 nanomembranes compared with TH from β-Ga2 O3 nanomembranes on glass substrates. The contribution of the TH field from the β-Ga2 O3 -air interface was found to be 5.12 times more efficient than that from the β-Ga2 O3 -glass interface, and also 1.09 times stronger than the TH excited at bulk 1-μm-thick β-Ga2 O3 . Besides, TH from the β-Ga2 O3 -air interface was found to be 20% more sensitive to the crystalline structure than that from the β-Ga2 O3 -glass interface. This research work deepens our understanding of surface and bulk THG from crystalline materials and provides new possibilities towards designing highly efficient nonlinear optical materials for bio-imaging, energy-harvesting, and ultrafast laser development.